Married and Cohabiting Finnish First-Time Parents: Differences in Wellbeing, Social Support and Infant Health - Kalland Mirjam; Salo Saara; Vincze Laszlo; Lipsanen Jari; Raittila Simo; Sourander Johanna; Salvén-Bodin Martina; Pajulo Marjaterttu (MDPI, 2022)
Cohabitation is more common than marriage when couples are expecting their first child in Finland. However, little is known about possible differences in wellbeing between the two groups. In this study, we examined differences in parental wellbeing, relationship satisfaction, infant health outcomes, and use of social support among cohabiting and married first-time parents. Survey data was collected from 903 parents during pregnancy and at one month postpartum. Cohabiting parents had more depressive symptoms than married parents. They were also less satisfied with their relationships and expressed less satisfaction with the quality of support they got from their partner. Cohabiting fathers did not use the cost-free support from maternity clinics as often as married fathers. Our results show differences in well-being between married and cohabiting first-time parents and that the support from maternity clinics should better acknowledge diversity and address the different needs of different types of families.